2020
DOI: 10.1007/s11046-020-00495-0
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of S. chartarum (Ehrenb.) S. Hughes Chemotypes A and S via FT-IR Spectroscopy

Abstract: Stachybotrys (S.) chartarum is a cellulolytic mould with the ability to produce highly cytotoxic macrocyclic trichothecenes. Two chemotypes are defined according to their ability to produce either atranones or satratoxins. S. chartarum has been well known as the causative agent of the lethal disease stachybotryotoxicosis in horses. Further investigations revealed that this disease is strictly correlated with the presence of macrocyclic trichothecenes. Furthermore, their occurrence in water-damaged buildings ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…By using protein spectrum analysis, the change of an individual strain and the formation of strain clusters can be recognized; thus, their spectra obtained by MALDI-TOF MS and from FT-IR proceeded to similarity analysis and the data was statistically evaluated. The mass spectrometry analysis was applied in this study, since previous studies have shown it to be highly reliable in terms of discriminatory power and the identification accuracy of microorganisms [33,[55][56][57]. Additionally, it requires less material and cost and is rather easy to be conducted with a high number of samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By using protein spectrum analysis, the change of an individual strain and the formation of strain clusters can be recognized; thus, their spectra obtained by MALDI-TOF MS and from FT-IR proceeded to similarity analysis and the data was statistically evaluated. The mass spectrometry analysis was applied in this study, since previous studies have shown it to be highly reliable in terms of discriminatory power and the identification accuracy of microorganisms [33,[55][56][57]. Additionally, it requires less material and cost and is rather easy to be conducted with a high number of samples.…”
Section: Discussionmentioning
confidence: 99%
“…For cell masses grown for shorter/longer periods or in other nutrient solutions, the FT-IR spectra sometimes differ considerably. Therefore, reproducible and meaningful information can only be expected from cell masses obtained under standardized conditions [32,33]. To ensure these standardized conditions during FT-IR measurement, all E. coli strains were cultured on the same medium, incubated at the same room temperature for exactly 24 h. The restrained growth of Campylobacter spp.…”
Section: Ft-irmentioning
confidence: 99%
“…chartarum, which are characterized and distinguished by the production of certain secondary metabolites. While the group of macrocyclic trichothecenes (MCTs, e.g., satratoxins) are only found in strains of chemotype S, atranones are only produced by strains of chemotype A. , Phenylspirodrimanes (PSDs) are produced by both chemotypes of S. chartarum and account for the most abundant group of metabolites produced by all known Stachybotrys species. …”
Section: Introductionmentioning
confidence: 99%
“…While the group of macrocyclic trichothecenes (MCTs, e.g., satratoxins) are only found in strains of chemotype S, atranones are only produced by strains of chemotype A. 5,6 Phenylspirodrimanes (PSDs) are produced by both chemotypes of S. chartarum and account for the most abundant group of metabolites produced by all known Stachybotrys species. 7−9 Phenylspirodrimanes (e.g., 1−3) are triprenyl phenols whose biosynthetic precursor LL-Z1272β (4, also known as ilicicolin B) is a well-known key intermediate in the biosynthesis of several meroterpenoid structures.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The previ ously mentioned mycotoxins are a diverse group of compounds that can cause inflamma tion and nephrotoxic, hepatotoxic, and genotoxic effects in mammals [12]. Especially, th highly toxic macrocyclic trichothecenes (MCTs), which represent one of three main com pound classes produced by Stachybotrys, are a suspected cause of potential disease [13,14]. Among the MCTs, satratoxins are often produced by Stachybotrys at the highes concentrations [15,16].…”
Section: Introductionmentioning
confidence: 99%